HBV Hepatitis and Related Renal Nephropathies: Pathogenesis and Treatment - Maurizio Salvadori; Aris Tsalouchos (Journal of Renal and Hepatic Disorders, 2020)
The extrahepatic manifestations of hepatitis B virus (HBV) infection include reactive arthritis, vasculitis (panarteritisnodosa), and primary glomer-ulonephritis (membranous nephropathy, membranoproliferative glomerulonephritis, and, less frequently, IgA nephropathy, focal and segmental glomerulosclerosis, and minimal change disease). No specific histomorphological patterns have been reported in association with HBV infection. The treatment of HBV-related glomerulopathies is essentially antiviral. Peginterferon and nucleos(t)ide drugs are the treatment of choice. Cortico-steroids have been proved to be ineffective (except in panarteritisnodosa), while immunosuppressants can lead to exacerbation of HBV infection.